2018
DOI: 10.3892/or.2018.6891
|View full text |Cite
|
Sign up to set email alerts
|

Docetaxel promotes cell apoptosis and decreases SOX2 expression in CD133‑expressing hepatocellular carcinoma stem cells by suppressing the PI3K/AKT signaling pathway

Abstract: Docetaxel is a front-line standard-of-care chemotherapeutic drug for the treatment of cancers. However, the underlying function and mechanism of docetaxel in human hepatocellular carcinoma (HCC) are uncertain. Therefore, the present study aimed to determine the effects of docetaxel on cell apoptosis and SOX2 expression in cultured human HCC stem cells. After human HCC stem cells were treated with docetaxel, cell proliferation was assessed by methyl thiazolyl tetrazolium (MTT) method, the cell apoptotic rate wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 41 publications
2
12
0
Order By: Relevance
“…We found increased SOX2 expression in HCC tissues in our study, which is in line with previous studies [ 14 , 15 ]. Moreover, we found that SOX2 was involved in HepG2 cell proliferation, migration, and invasion, also in agreement with a previous study [ 9 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found increased SOX2 expression in HCC tissues in our study, which is in line with previous studies [ 14 , 15 ]. Moreover, we found that SOX2 was involved in HepG2 cell proliferation, migration, and invasion, also in agreement with a previous study [ 9 ].…”
Section: Discussionsupporting
confidence: 93%
“…Recently, SOX2 has been linked to cancer progression due to its effects on cell proliferation, invasion, and migration properties [ 10 ], with well-established involvement in prostate and cervical cancers [ 11 , 12 ], and likewise in the case of HCC development [ 13 15 ]. Previous work has shown that activation of the PI3K/AKT signaling pathway could up-regulate SOX2 expression of human HCC stem cells [ 14 ]. Furthermore, high SOX2 expression is associated with the prediction of poor survival in HCC patients [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Here, we observed that 4MU increased the pro-apoptosis genes Bax and Puma, while decreased the anti-apoptosis gene Bcl2a in Huh7. It was known that CSC CD133 is correlated with anti-apoptosis property 48,49 . However, the effect of 4MU in the epithelial mesenchymal transition (EMT), another hallmark of CSC, was unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Current studies demonstrate that Regorafenib, Cabozantinib, and Ramucirumab are appropriate supplements for sorafenib as second-line therapy in patients with advanced HCC who are resistant, progressive, or intolerant to sorafenib; [ 7 ] Also the increase of SRY-Box Transcription Factor 2 ( SOX2 ) gene expression is related to the occurrence and development of HCC. [ 8 ] However, more core genes associated with hepatocellular carcinoma are unknown.…”
Section: Introductionmentioning
confidence: 99%